2009
DOI: 10.2478/s11532-008-0094-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrosynthesis and thermal characterization of basic copper carbonate nanoparticles

Abstract: Abstract:The present study concerns the electrochemical synthesis of basic copper carbonate nanoparticles by oxidation of metallic copper on the anode in an aqueous bicarbonate solution. This simple and one-step preparation can be considered as green synthesis. The scanning electron microscopy (SEM) analysis indicates that average particle size of the product is in the range of about 70 nm.On the other hand, basic copper carbonate micro-powder has been prepared, by mixing solutions of copper(ΙΙ) sulphate and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Some researchers have synthesised copper oxide nanoparticles by the electrochemical method; Yuan et al [35] used copper plate as anode and stainless steel as cathode; the electrolyte was 200 mM NaNO 3 . Yang et al [37] used copper slice electrodes in 2 M NaCl, 0.5 g/L NaOH and 0.04 g/L K 2 Cr 2 O 7 to generate Cu 2 O at 70 C. Pourmortazavi et al [36] obtained basic copper carbonate nanoparticles by electrosynthesis using NaHCO 3 . In this study, an attempt has been made to synthesise CuO nanoparticles by electrochemical-thermal method using the same metal electrodes (anode and cathode) and electrolyte without metal salt, at ambient temperature.…”
Section: Influence Of Electrolytementioning
confidence: 99%
See 1 more Smart Citation
“…Some researchers have synthesised copper oxide nanoparticles by the electrochemical method; Yuan et al [35] used copper plate as anode and stainless steel as cathode; the electrolyte was 200 mM NaNO 3 . Yang et al [37] used copper slice electrodes in 2 M NaCl, 0.5 g/L NaOH and 0.04 g/L K 2 Cr 2 O 7 to generate Cu 2 O at 70 C. Pourmortazavi et al [36] obtained basic copper carbonate nanoparticles by electrosynthesis using NaHCO 3 . In this study, an attempt has been made to synthesise CuO nanoparticles by electrochemical-thermal method using the same metal electrodes (anode and cathode) and electrolyte without metal salt, at ambient temperature.…”
Section: Influence Of Electrolytementioning
confidence: 99%
“…Recently, the ZnO nanoparticles have been bulk synthesised by electrochemical method [34]. Also, CuO nanoparticles are synthesised using Cu as sacrificial anode and steel as cathode [35,36] and Cu as anode and cathode [37] in different electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…Cuminaldehyde (Anklam et al, 1998;Azizi and Davareenejad, 2009;Mortazavi et al, 2010;Pourmortazavi et al, 2003Pourmortazavi et al, , 2004Salehi et al, 2008;Stashenko et al, 1996). Pourmortazavi et al (2005) have also compared the percentage of cuminaldehyde obtained from hydrodistillation and SCF. They reported that cuminaldehyde was detected in both extraction methods, though in SCF it was at lower level.…”
Section: Effect Of Solvent Extraction On Concentration Of Cuminaldehydementioning
confidence: 99%
“…In an indigenous remedy, seeds are regarded as stimulants, carminatives and found to be useful in diarrhea and dyspepsia treatment (Foroumadi et al, 2002). In addition, the plant is used for culinary purposes, flavoring foods and beverages (Pourmortazavi et al, 2005). It is also reported that Black zira seeds contain essential oils (up to 7%) rich in monoterpene aldehydes.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, the electrochemical method of synthesis of nanosized metal oxide powder and films have acquired a considerable interest because of its simplicity, low operating temperature and viability in commercial production. Recently, ZnO and CuO nanocrystals have been successfully synthesized by electrochemical route [38][39][40][41]. Thus, designing a suitable method for preparing CuO at ambient temperature with narrow particle size distribution, better properties and reduced operating costs are appropriate research endeavors.…”
Section: Introductionmentioning
confidence: 99%